Flexural Behavior of Reinforced Concrete Beams with Varying Carbon Content in Steel - Marsella, A. Adelia; Djamaluddin, Rudy; Fakhruddin (Engineering, Technology & Applied Science Research, 2026)
This study examines the influence of carbon content in reinforcing steel on the flexural behavior of reinforced concrete beams subjected to two-point loading. Three categories of reinforcing steel were investigated: low-carbon (0.302%), medium-carbon (0.318%), and high-carbon (0.411%), with three beam specimens tested for each type. The average ultimate loads (Pu) were 48.78 kN for Low-Carbon Bars (LCB), 57.39 kN for Medium-Carbon Bars (MCB), and 62.28 kN for High-Carbon Bars (HCB). The corresponding average mid-span deflections at ultimate load were 85.14 mm, 51.09 mm, and 47.72 mm, respectively. An increase in carbon content resulted in an approximately 28% increase in ultimate strength from LCB to HCB, accompanied by a 54% reduction in ductility (μ). In terms of structural response, LCB beams exhibited significant plastic deformation and gradual flexural crack development, indicating high energy dissipation capacity. MCB beams demonstrated a balanced combination of strength and ductility. In contrast, HCB beams achieved the highest strength but exhbited limited post-yield deformation and more pronounced crack localization.